2020
DOI: 10.1186/s12887-020-02353-w
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated skeletal maturation is associated with overweight and obesity as early as preschool age: a cross-sectional study

Abstract: Background Body mass index (BMI) and skeletal age (SA) are important indicators of individual growth and maturation. Although the results have not been unified, most studies indicated that accelerated skeletal maturation is associated with overweight/obesity. However, there have so far been insufficient studies about the association between accelerated skeletal maturation and overweight/obesity in preschoolers, particularly Asian children. A cross-sectional study was conducted on Chinese childr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…BA was advanced more than 2 years in 33% of obese children compared with only 1% of nonobese children [ 57 ]. Another study also observed the effect of obesity on BA advancement, specifically among preschool children (age 3-6 years) [ 59 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…BA was advanced more than 2 years in 33% of obese children compared with only 1% of nonobese children [ 57 ]. Another study also observed the effect of obesity on BA advancement, specifically among preschool children (age 3-6 years) [ 59 ].…”
Section: Questions Addressed and Suggestionsmentioning
confidence: 99%
“…Prepubertal BA is accelerated in obese children (2)(3)(4)(5), presumably due to increased insulin secretion (3). In this study, the median BMI SD scores among 6-and 7-yr-olds in the FSS group exceeded 0, unlike in the other two groups.…”
Section: Discussionmentioning
confidence: 46%
“…The CA with the greatest BA delay was 9 yr, 8 yr, and 7 yr in the ISS, FSS, and SGA groups. Adrenal androgen affects bone maturation in prepubertal children (5)(6)(7). It is well known that adrenarche starts early in children born SGA (18), but there have been no reports concerning the timing of adrenarche in children with ISS or FSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,15,16 Conversely, others have shown that the combined effect of multiple hormones influences skeletal maturation. 17,18 The inconsistent findings in existing studies might be attributed to the differences in ethnicity, sample size, nutritional status of the populations, investigations timing and the instruments and methods used to measure hormone levels. 19 To gain comprehensive insights, this study aimed to analyse the association between sex hormones and BA in Chinese boys aged 9-18 years, both individually and interactively, and further to explore the potential effect of nutritional status on this association.…”
mentioning
confidence: 99%